A 3D-printed prosthetic hand with modular reconfigurable fingers - Mio R. (2019)
Partial hand and transradial amputations are among the most common levels of amputation. In the former case, a mechanical prosthesis is prescribed, while in the latter case either a mechanical or a myoelectric one are used depending on the patient’s preference and access to the technology. While a variety of prostheses designs are aimed to transradial amputees and plenty others are for partial hand amputations, like the 3D-printed open-source concepts that are activated by the user’s wrist, for a faster and more efficient treatment of hand amputations, one design should be adaptive for different levels of amputation without compromising the prosthesis performance. This work describes a powered prosthesis design with modular fingers and space constraints that allow it to be adapted to different levels of amputation. The prosthesis finger lengths could also be customized to user-specific anthropometry and, besides shafts, bolted connections and electronic components, the whole hand can be 3D printed.